'Seeing is believing, but not necessarily perceiving!': Chinese EFL M.E.d. student teachers' perceptions of school visit experiences. Issue 1 (1st January 2021) - Yan, Chunmei; He, Chuanjun
ABSTRACT: School experience has been practised as an integral component of undergraduate teacher education programmes in many countries. This has spurred a large amount of research on various issues in the whole experience. However, the stage of school visits and classroom observations remains unexplored as a research subject. This paper reports on a study of a group of Chinese EFL (English as a foreign language) M.E.d. student teachers' perceptions of their year-long experience of school visits. It was found that, whilst the student teachers benefited from the experience, such as increased familiarity with school life, an enhanced motivation for professional development, and an emerging collaborative community, three limitations emerged in the process, including limited professional experiences and understanding, potential oscillation from an idealistic to realistic mindset, and the limited depth of collaboration. Therefore, the study indicates that extensive school visits experience alone is insufficient, and should be offered in tandem with well-structured reflective teaching practicum to facilitate student teachers' gradual teacher identity formation. Dynamic and systematic partnerships are necessary to set concrete goals and assessments at each stage, and make curricular and pedagogical transformations responsively.